To Detect the Dyslipidemia in Patients with Rheumatic Arthritis (Medical Forum Monthly, 2024)
Objective: To determine the abnormalities of lipid profile in patients with rheumatic arthritis. Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted in the Department of Medicine, Peoples University of Medical and Health Science, Nawabshah and MMC Mirpur khas from 2011 to 2013.Materials and Methods: Total 48 patients with RA were selected. All the equitable investigation was done. The patients were chosen for the study after a brief medical history. Patients with smoking and alcohol habits, those suffering with systemic disease like diabetes mellitus, hypertension and those on corticosteroids, statins, immunosuppression and vitamins supplementation, liver, kidney, thyroid abnormalities, ischemic heart disease, pregnant and post menopausal women were excluded. Lipid profile HDL, LDL, TC and TG were checked in all the cases after an overnight fasting of 12 hours. All the data was entered in the written proforma.Results: Total 48 cases were selected in the study after diagnosis of RA, mean age of the cases was found 36.5+7.2 years, female found in the majority 30/62.5%, mostly patients were married 35/72.9.A significant difference was found in the lipid profile, HDL was found low in majority of cases 17/35.4%, while TG was high in the majority of the patients 15/31.2%.Conclusion: In the conclusion of this study dyslipidemia is highly associated with RA disease. In patients with RA disease lipid profile should be checked necessarily, to reduce the morbidity and mortality due to cardiovascular disease.